Charles Dickens, educação infantil e democracia: uma visão de formação de indivíduos em Oliver Twist e Hard Times - Santurio, Roberta Flores (2020)
The present work investigates the critical view of Charles Dickens (1812-70) on the subject Education as presented in Oliver Twist (1838) and Hard Times (1854). The description of the Victorian experience of education, which finds its initial critique in Dickens's work, provides a glimpse of still-existing problems, including the relationship between education and sensitivity, education and authoritarianism, education and freedom. When we focus the analysis on the children and on the representatives of education, we realize that Dickens's pedagogical ideal, as presented in the two narratives, envisions a broad development of individuals, through democratic teaching methods. It is important to highlight that the term ‘democracy’ is not held as a form of government, but rather as an educational philosophy which includes both body and mind. Thus, in the dickensian view, a broad education which aims in the improvement of character, is the path which could lead us to a collective unity. However, as we analyzed, Oliver Twist, one of the author's first novels, is configured by the high level of idealization and is based essentially on Christian values. On the other hand, Hard Times is incisive in its criticism of the Utilitarian doctrine and attempts to a movement towards social action. Despite the differences in the tone of the narratives, both advocate for individual and social balance, depicting an author with gregarious principles. In order to articulate the values established in the nineteenth-century English educational process along with Dickens' social criticism, the analysis considers some ideas of Jeremy Bentham and John Stuart Mill, two of the leading utilitarian thinkers and philosophers active in the educational setting of the period.